Distribution power system reconfiguration using whale optimization algorithm - Mahmoud Soliman; Almoataz Y. Abdelaziz; Rabab M. El-Hassani (International Journal of Applied Power Engineering (IJAPE), 2020)
This study discusses how to enhance the power distribution system and one of the most important ways to do that is by reconfiguration of the power system. Reconfiguration means changing the topology of the radial distribution network by changing the status of switches. The objective is to minimize the total power loss and enhance the voltage profile. Many optimization techniques were used to solve this problem such as classical optimization which is proven to be time consuming method and heuristic methods which are more efficient in our problem here. In this paper, the whale optimization algorithm (WOA) which is one of the modern heuristic optimization techniques and it has high efficiency to solve discrete optimization problems, is used to get the optimum case in reconfiguration problem. WOA is applied to (33 bus system, 69 bus system, and 118 bus system) and results are compared to other heuristic methods.